Aplikasi Web Perhitungan Kelayakan Finansial Pada Agrowisata Desa Kreatif Bingin Ambe Koripan - Dewi, Ni Made Gusnia; Sugiartawan, Putu (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2022)
Agricultural tourism is a tourist destination built with a theme or concept that combines agricultural activities and commercial activities. One of the livestock tourism development plans is Br. Anyar, Kediri District, Tabanan Regency. It is not yet known whether the tourism category is feasible or financially feasible, so an economic feasibility analysis is carried out. The purpose of the analysis and execution of this feasibility calculation application is to determine the profitability of an object or category that will later be applied to agro-tourism. Only three investment evaluation methods are used in this study. The three methods are payback period, present value and internal rate of return. The results obtained in this study were that Strawberry Picking Tourism was stated to be profitable with PP results for 33 months, NPV 14,537,100 and IRR 25.02%. The Bike Rental category was declared profitable: PP results for 24 months, NPV 36,346,700 and IRR 45.23%. The picnic area category with the results obtained is PP for 16 months, NPV 58,223,500 and IRR 77.85%. The Food & Beverage Division was declared profitable with PP results for 88 months, NPV 13,460,300 and IRR 10.44%. From this it can be concluded that all classes are feasible and can be implemented. A web-based financial perspective calculation system that can be used to calculate whether an investment is feasible or not.